RuPhos Pd Precatalyst and MIDA Boronate as an Effective Combination for the Precision Synthesis of Poly(3-hexylthiophene): Systematic Investigation of the Effects of Boronates, Halides, and Ligands - Lee, Jaeho; Park, Hyunwoo; Hwang, Soon Hyeok; Lee, In Hwan; Choi, Tae Lim (Macromolecules, 2020)
Herein, we report detailed mechanistic studies of Suzuki-Miyaura catalyst-transfer polycondensation (SCTP) of thiophene. The effects of boronates, halides, ligands, and chain transfer agents (CTAs) on the control of polymerization were systematically investigated in detail by SEC, 1H NMR and MALDI-TOF analyses. Initially, we identified that the use of the slow-hydrolyzing N-methyliminodiacetic acid (MIDA) boronate in place of conventional pinacol boronate effectively suppressed side reactions such as protodeboronation, homocoupling, and chain transfer reactions, thereby improving control of SCTP. Screening halides revealed that the monomer containing bromide was optimal for SCTP, resulting in less side reactions. Moreover, screening several ligands and adding a CTA further supported our conclusion that the RuPhos-Pd system showed the best catalyst-transfer ability among the tested catalysts. We further elucidated that externally added ligands effectively stabilized living chain-ends and suppressed chain transfer, thereby achieving controlled polymerization.
Keywords: Catalyst transfers; Chain transfer agents; Chain-transfer reactions; Controlled polymerization; Mechanistic studies; Poly (3-hexylthiophene); Side reactions; Suzuki-Miyaura